2019
DOI: 10.1177/0333102419883355
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of episodic migraine transformation to chronic migraine: A systematic review and meta-analysis of observational cohort studies

Abstract: Background and purpose An estimated 2.5–3.1% of people with episodic migraine develop chronic migraine in a year. Several risk factors are associated with an increased risk for this transformation. We conducted a systematic review and meta-analysis to provide quantitative and qualitative data on predictors of this transformation. Methods An electronic search was conducted for published, prospective, cohort studies that reported risk factors for chronic migraine among people with episodic migraine. Risk of bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 53 publications
0
35
0
4
Order By: Relevance
“…However, previous epidemiological studies have identified risk factors for progression to CM. These established risk factors include overuse of medications such as triptans, high headache frequency, allodynia, obesity, caffeine consumption, snoring, depression, neck/head trauma, and other comorbidities [12][13][14][15][16][17][18][19][20] . Socioeconomic factors such as low income and low education were found to be significantly associated with progression of migraine 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, previous epidemiological studies have identified risk factors for progression to CM. These established risk factors include overuse of medications such as triptans, high headache frequency, allodynia, obesity, caffeine consumption, snoring, depression, neck/head trauma, and other comorbidities [12][13][14][15][16][17][18][19][20] . Socioeconomic factors such as low income and low education were found to be significantly associated with progression of migraine 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…AMO is associated with the risk of migraine disease progression from episodic migraine (EM) to chronic migraine (CM). 9 , 13 , 28 , 29 In the AMPP study, triptan overuse alone was associated with risk of disease progression from EM to CM depending on the baseline frequency of MHDs; however, triptan use in combination with NSAIDs was not associated with an increased risk of progression, and NSAID use may be protective of progressing from EM to CM depending on MHDs. 13 , 28 , 30 In addition, opioids and barbiturate analgesics are associated with dose-dependent increased risk of CM onset across a range of frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic migraine (CM) is a highly disabling condition that frequently manifests as a negative evolution of episodic migraine (EM) in a process that takes place over years [1]. In a recent meta-analysis on the predictors of migraine chronification, a number of monthly headache days ≥ 10 showed the strongest level of evidence, with depression and low household income being supported by moderate evidence [2]. In the same meta-analysis, medication overuse (MO) was associated to the highest risk ratio in a random-effects model (RR 8.82; 95% CI, 2.88-27), although the strength of evidence was rated 'very low'due to substantial heterogeneity among studies.…”
Section: Introductionmentioning
confidence: 99%